2002
DOI: 10.1159/000051830
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intralesional 5-Fluorouracil in the Treatment of Keloids

Abstract: Background: The treatment of keloids remains challenging. Cryosurgery and intralesional corticosteroids have been considered as the mainstream of therapy; however, the long-term use of corticosteroids has been found to be associated with serious side effects. Intralesional 5-fluorouracil (5-FU) has only been used in one study for the treatment of hypertrophic scars and keloids, mostly in combination with other treatments. The efficacy of 5-FU as an individual therapeutic agent is unknown. Objective: To evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(130 citation statements)
references
References 9 publications
4
116
1
9
Order By: Relevance
“…Ulceration and tissue sloughing were seen in 65% of the patients, which took a few weeks to heal. This has been observed in other studies also [1,[4][5][6]. None of these side effects were seen with triamcinolone acetonide injection, so the patient compliance was much more in the latter group.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Ulceration and tissue sloughing were seen in 65% of the patients, which took a few weeks to heal. This has been observed in other studies also [1,[4][5][6]. None of these side effects were seen with triamcinolone acetonide injection, so the patient compliance was much more in the latter group.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies evaluating intralesional steroids have reported roughly a 50% recurrence rate [2,3]. In the recent past, intralesional 5-FU has been tried in hypertrophic scars and keloids in combination or as an individual therapeutic agent [1,[4][5][6]. A paucity of literature is available regarding the usefulness and safety profile of 5-FU as an individual therapeutic agent [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es wird einmal wöchentlich mit einer Dosis von 50 mg/ ml über 12 bis maximal 16 Wochen intraläsional appliziert, wo− bei eine Gesamtdosis von 50 ± 150 mg pro Sitzung nicht über− schritten werden soll. Durch eine Inhibition der Fibroblastenpro− liferation kommt es zur einer signifikanten Abflachung der Ke− loide, bei bis zu 50 % der Patienten, wie Gupta und Kalra berich− ten [23]. Mögliche Nebenwirkungen sind Hautirritationen, Schmerzen während der Injektion, Ulzerationen und Purpura.…”
Section: Intraläsionale Zytostatikaunclassified
“…The symptoms disappeared in 17 (70.8%) patients and improved in 3 (12.5%) patients. 27 Kontochristopoulos et al in his study found that out of 20 patients, 17 (85%) patients showed more than 50% improvement. 28 Darougheh et al in his study patient's self-assessment at end of study showed > 50% improvement in 55% patients among Group 1.…”
mentioning
confidence: 91%